Training on Providing Additional Food For Prospective Mothers As The Importance of Balanced Nutrition 1000 HPK - Bernadetha, Bernadetha; Pramono, Joko Sapto; Palin T, Yona (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2024)
According to data from the Health Center Profile, the majority of the population at the trauma center, specifically 10,327 individuals, or 49.1%, are private employees. At the same time, the smallest group, consisting of only 28 people, are scavengers. The health center employs 67 health workers, while the trauma center has 35 integrated health posts, with one integrated health post housing 6 people. In 2022, the prevalence of balanced nutrition in East Kalimantan will be 23.9%, placing it 16th among 34 provinces in Indonesia (SSGI, 2022). In Samarinda City, the prevalence of stunting is 25.3% (SSGI, 2022). This makes the government more aggressive and focused on the stunting problem. However, underweight and wasting strongly influence stunting in East Kalimantan; a decrease in underweight and wasting also reduces stunting. The challenges include a lack of achievement targets for balanced nutrition in the Trauma Center Health Centre's work area, which can be attributed to economic factors and parenting patterns that affect food provision. The Trauma Center Health Center faces several challenges, including a lack of knowledge among health workers, a low community economy, and suboptimal participation from health workers in promoting balanced nutritional health. This study aims to enhance the understanding and accessibility of balanced dietary food for prospective mothers by facilitating simulations and demonstrations of food portioning techniques.